2018
DOI: 10.1111/ppa.12940
|View full text |Cite
|
Sign up to set email alerts
|

A study of viral coat protein accumulation in lily chloroplasts from mixed virus infections of Lily mottle virus and Cucumber mosaic virus

Abstract: Two viruses that frequently occur in many Lilium species are Lily mottle virus (LMoV) and Cucumber mosaic virus (CMV), which usually co‐infect lilies causing severe disease symptoms. Recent reports have revealed that the viral coat protein (CP) affects chloroplast ultrastructure and symptom development. This study used western blot analysis to confirm that in leaves infected by mixed virus infections of LMoV and CMV, CPs of both viruses were accumulated in lily chloroplasts. Immunogold labelling further demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Immunogold labeling has revealed Lily mottled virus coat protein localized to chloroplasts. The overaccumulation of this protein inhibits PSII activity, causing mottling symptoms (Zhang et al 2019). The studies described above showed correlations between photosystem damage and chlorotic symptoms; our results support these findings.…”
Section: Discussionsupporting
confidence: 88%
“…Immunogold labeling has revealed Lily mottled virus coat protein localized to chloroplasts. The overaccumulation of this protein inhibits PSII activity, causing mottling symptoms (Zhang et al 2019). The studies described above showed correlations between photosystem damage and chlorotic symptoms; our results support these findings.…”
Section: Discussionsupporting
confidence: 88%
“…LSV and its co-infections with CMV or LMoV have been reported in various endemic regions worldwide. Some of the regions where these viruses have been identified include: the Netherlands, China, Japan, and the United States [21,27,98]. Mixed infection with these viruses leads to severe symptoms like smaller flowers, lower bulb yield, and growth reduction.…”
Section: Reverse Transcription Loop-mediated Isothermal Amplificationmentioning
confidence: 99%
“…Consequently, the ID-ELISA method and IC-RT-PCR assays have been developed for efficient lily virus detection [104]. These methods were recommended for further control, surveys, and also to prevent lily infection by most of the viruses that occur in Lanzhou/Gansu Province and NingXia, the most important lily production areas in China [21,98]. Next-generation sequencing: This is a high-throughput sequencing technique that can detect and identify viral sequences in a sample.…”
Section: Generation and Purification Of Recombinant Coat Proteinsmentioning
confidence: 99%